The cnidome and ultrastructural morphology of late planulae in Lophelia pertusa (Linnaeus, 1758)—With implications for settling competency. (9th April 2019) - Strömberg, Susanna M.; Östman, Carina; Larsson, Ann I.
Abstract: The larval pre‐competency period and competency window are important in delimiting the potential dispersal distance for pelagic larvae of sessile marine fauna. Here, we provide evidence for morphological changes in the late planulae of Lophelia pertusa that have implications for their dispersal potential. Three weeks after spawning, the planulae gain functional cnidocysts, indicating that they are competent to settle at this time. Cnidae have been shown to be used for primary anchoring during settling, and before this time point, the larvae most probably do not have the ability to attach to a substrate in high flow conditions. The appearance of functional cnidae coincides with larvae gaining a flexible mouth that can be opened to the full width of the larva. The larval isorhizas differ the most from the adult polyps isorhizas, while the p‐ and b‐mastigophores bear more resemblance to the adult homologues of similar size. The external and internal morphology of late planulae is further described with demonstration of long apical cilia and its effect on swimming agility, morphological changes of the ciliated cells in the larval mouth region and an internal nerve plexus. This study also indicates that L. pertusa planulae seek out cryptic spaces for settling.